Myron I. Lichtblau, The Argentine novel in the nineteenth century. Hispanic Institute, New York, 1959; 228 pp. - Carilla, Emilio (El Colegio de México, 2007)
Se reseñó el libro: The Argentine novel in the nineteenth century.